2022
DOI: 10.3390/nu14214580
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Dietary Magnesium and Prediabetes in Childbearing Chinese Women: Results from China Nutrition and Health Surveillance (2015–2017)

Abstract: Although several studies have shown the relationship between magnesium and diabetes, there are few studies regarding the association between magnesium status and prediabetes. This study aimed to examine the association between dietary magnesium intake and the risk of prediabetes in childbearing Chinese women (18–44 years). A total of 1981 participants without diabetes were randomly selected from China Nutrition and Health Surveillance (CNHS) in 2015 by considering the regional types and monitoring points, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…We also explored the possible threshold of dietary magnesium in the prevention of T2DM by a restricted cubic spline regression. It was found that there was a significant association with T2DM when the diet Mg intake was less than 408 mg/d [38]. This threshold is very close to our team's previously published research, with a threshold of 410 mg/d for dietary magnesium in the prevention of prediabetes.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We also explored the possible threshold of dietary magnesium in the prevention of T2DM by a restricted cubic spline regression. It was found that there was a significant association with T2DM when the diet Mg intake was less than 408 mg/d [38]. This threshold is very close to our team's previously published research, with a threshold of 410 mg/d for dietary magnesium in the prevention of prediabetes.…”
Section: Discussionsupporting
confidence: 84%
“…However, a cross-sectional study concluded that more than 300 mg/d of Mg intake might not improve insulin sensitivity and have no influence [41]. The difference in the dietary magnesium threshold may be due to different dietary survey methods (including 3 days, 24 h, and FFQ) [38] and statistical methods, and another may be due to differences among study populations. However, unlike other studies, we further analyzed the threshold effects of dietary and plasma Mg on T2DM and found a good consistency between plasma and dietary Mg.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Maintaining an appropriate serum magnesium level is crucial for diabetic patients, as it plays a significant role in glucose and insulin metabolism. 6 Researches 7 , 8 indicate that low serum magnesium levels may contribute to insulin resistance and increase the risk of diabetes.…”
Section: Introductionmentioning
confidence: 99%